The 48 laws of power - Greene, Robert (New York Viking, 2000)
Drawn from 3,000 years of the history of power, this is the definitive guide to help readers achieve for themselves what Queen Elizabeth I, Henry Kissinger, Louis XIV and Machiavelli learnt the hard way. Law 1: Never outshine the master Law 2: Never put too much trust in friends; learn how to use enemies Law 3: Conceal your intentions Law 4: Always say less than necessary. The text is bold and elegant, laid out in black and red throughout and replete with fables and unique word sculptures. The 48 laws are illustrated through the tactics, triumphs and failures of great figures from the past who have wielded - or been victimised by - power.
Includes bibliographical references (p. 431-432) and index.
Keywords: Power (Philosophy)